Historical Roots Of Youth Education In The Spirit Of Friendship And Humanism In Folk Pedagogy - Gulbahar Bekimbetova; Gulnara Temirkhanova (Zien Journals, 2022)
This article provides information about the historical roots of the Karakalpak folk pedagogy in the education of young people in the spirit of friendship and philanthropy. A peculiar feature of the methods of direct pedagogical influence on youth and intensive methods of education is revealed
Keywords: ethnopedagogy; tolerance; folk culture; altruism